Effectiveness of the Deep Learning Oriented FIVES Model in Improving Fifth Grade Elementary Students' Reading Literacy - Tantris, Intan Ega; Puspita, Ryan Dwi; Kustiana, Kustiana (Program Magister Teknologi Pendidikan Universitas Jambi, 2026)
This study aims to analyze the effect of the Deep Learning-oriented FIVES model on the reading literacy skills of elementary school students. This study uses the Research and Development (R&D) research method with the Borg and Gall model. The research subjects consisted of fifth-grade students of SDN Wanakerta for limited testing, and 60 fifth-grade students of SD Negeri Purwadadi II for extensive testing. The instrument used was a reading literacy ability test in the form of a pretest and posttest. Data analysis was carried out through normality tests, Mann-Whitney tests, N-Gain tests, and effect size calculations. The results showed that there was a significant difference in reading literacy skills between the experimental class and the control class after the intervention (sig. = 0.004 < 0.05). The average increase in N-Gain in the experimental class was 57.96% (quite effective category), while in the control class it was 33.38% (less effective category). The effect size calculation showed a value of r = 0.66 which is included in the large category. These findings indicate that the Deep Learning-oriented FIVES model has a significant and strong influence on improving elementary school students' reading literacy skills.